Development of an economic and mathematical model for the optimal development of gas supply systems - Aimatov, Rustam Ruzibaevich; Mamatov, Bakir Botiruli; Barotov, Qobuljon (European Journal of Life Safety and Stability (2660-9630), 2021)
The article presents the results of feasibility studies of gas distribution systems for small settlements and agricultural facilities under conditions of temporary use of liquefied hydrocarbon gas with the subsequent transfer of consumers to the supply of networked natural gas. Recommendations are given for determining the maximum distance at which it is advisable to transfer a consumer gasified with liquefied gas to natural gas.